2007
DOI: 10.1667/rr0701.1
|View full text |Cite
|
Sign up to set email alerts
|

Initial Yields of DNA Double-Strand Breaks and DNA Fragmentation Patterns Depend on Linear Energy Transfer in Tobacco BY-2 Protoplasts Irradiated with Helium, Carbon and Neon Ions

Abstract: The ability of ion beams to kill or mutate plant cells is known to depend on the linear energy transfer (LET) of the ions, although the mechanism of damage is poorly understood. In this study, DNA double-strand breaks (DSBs) were quantified by a DNA fragment-size analysis in tobacco protoplasts irradiated with high-LET ions. Tobacco BY-2 protoplasts, as a model of single plant cells, were irradiated with helium, carbon and neon ions having different LETs and with gamma rays. After irradiation, DNA fragments we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…Here, irradiation of the higher-LET proton beam (1.461 keV· m ). This result is consistent with a previous report in that an increased DNA breakage yield in the higher-LET radiation treatment was detected, in comparison with helium ion beam (9.4 and 17.7 keV· m -1 ) and lower-LET carbon ion beam (94.8 and 124 keV· m -1 ) (Yokota et al, 2007). Comparing the lower-LET proton beam and gamma ray, treatment with the lower-LET proton beam resulted in a similar proportion of damaged and undamaged DNA to gamma ray, but generated a smaller portion of short DNA fragments which was represented by smaller tails in the comet-shaped DNA spots.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Here, irradiation of the higher-LET proton beam (1.461 keV· m ). This result is consistent with a previous report in that an increased DNA breakage yield in the higher-LET radiation treatment was detected, in comparison with helium ion beam (9.4 and 17.7 keV· m -1 ) and lower-LET carbon ion beam (94.8 and 124 keV· m -1 ) (Yokota et al, 2007). Comparing the lower-LET proton beam and gamma ray, treatment with the lower-LET proton beam resulted in a similar proportion of damaged and undamaged DNA to gamma ray, but generated a smaller portion of short DNA fragments which was represented by smaller tails in the comet-shaped DNA spots.…”
Section: Discussionsupporting
confidence: 93%
“…Comparing the lower-LET proton beam and gamma ray, treatment with the lower-LET proton beam resulted in a similar proportion of damaged and undamaged DNA to gamma ray, but generated a smaller portion of short DNA fragments which was represented by smaller tails in the comet-shaped DNA spots. Yokota et al (2007) reported that the proportion of short DNA fragments was larger in treatments with high-LET heavy ion beam such as carbon and neon beam than with gamma ray, implying that higher-LET radiation may result in more closely spaced double-strand breaks in the DNA, and thus might result in severe chromosomal aberrations. In their research, helium ion beam, which show comparatively low-LET, caused similar DNA fragmentation patterns to gamma ray.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high yield of DSBs after heavy-ion beam irradiation was revealed by experiments on both animal and plant cells [19,20]. Therefore, significant DNA damage is likely to be caused by heavy-ion irradiation, although sequencing analysis of heavy-ion-induced DNA alterations is limited.…”
Section: Introductionmentioning
confidence: 99%
“…22) Initial DSB yields depended on LET and highest RBE was obtained at 124 and 241 keV/μm with carbon ions. It was also observed that ion beams yielded short DNA fragments of several hundred kbp more frequently than gammarays.…”
Section: Relative Biological Effectivenessmentioning
confidence: 94%